Evaluation of the CMV RNA elite MGB kit for monitoring CMV infections in pediatric solid organ transplant - M. Arosio; I. Passera; E. Nicastro; D. Guarneri; M. Fazioli; G. Napolitano; L. D'Antiga; C. Farina (Microbiologia Medica)
Not available.